2014
DOI: 10.1002/dc.23168
|View full text |Cite
|
Sign up to set email alerts
|

Atypical blast morphology of primary plasma cell leukemia with renal involvement and plasmablasts in urine

Abstract: Primary plasma cell leukemia (PCL) is a rare and aggressive variant of plasma cell (PC) myeloma characterized by high levels of circulating PCs. Clinical presentation is like other acute leukemia, with extramedullary infiltration of various tissues and organs being a frequent complication. The disease has a fulminant course and poor prognosis. Morphology of PCs in PCL includes a spectrum of maturity, with most cases having lymphoplasmacytoid or plasmablastic morphology. Presentation as more primitive cells tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Non-secretory type is therefore considered a rare subtype of PCL (2). Our literature review found only six previously published case reports on non-secretory pPCL with atypical morphology (Table 3) (11-16). Leukemic plasma cells were CD38- and CD138-positive but CD56-negative in most cases.…”
Section: Discussionmentioning
confidence: 99%
“…Non-secretory type is therefore considered a rare subtype of PCL (2). Our literature review found only six previously published case reports on non-secretory pPCL with atypical morphology (Table 3) (11-16). Leukemic plasma cells were CD38- and CD138-positive but CD56-negative in most cases.…”
Section: Discussionmentioning
confidence: 99%